Barriers to Fair and Effective Congressional Representation in Indian Country (Fourth World Journal, 2025)
Native American tribal nations may have survived in the face of 500 years of violent displacement as a result of European colonization, but have undergone profound changes to their land bases and ways of life. Settler colonialism is an imposed structure within which tribes have been forced to negotiate their circumstances, with Congress being one of the primary instruments of the settler state. This essay argues that there are several barriers inherent in the political system that precludes fair and effective Congressional representation, and that there are certain fundamental problems associated with tribes’ limiting themselves to working within the domestic system.